Assessment of the anti-inflammatory, analgesic and sedative effects of oleuropein from Olea europaea L - Mao, Xincheng; Xia, Bing; Zheng, Mingzhi; Zhou, Zhiming (Cellular and Molecular Biology, 2019)
More and more studies show that inflammation, pain and insomnia have become the main common diseases. Effective treatments of inflammation, pain and insomnia have become an issue of primary concern in clinical practice. Oleuropein (OLE), the main phenolic component of Mediterranean extra virgin olive oil, has shown many pharmacological properties. In the present study, the anti-inflammatory effect of OLE was firstly evaluated using RAW264.7 macrophages subjected to stimulation with lipopolysaccharide (LPSC). The results obtained revealed that OLE caused significant and dose-dependent downregulation of nitric (NO), COX-2, inducible NO synthase iNOS, and the inflammation-associated cytokines IL-6 and TNF-Î±. From the mechanism, the expression of COX-2, cytokines IL-6 and TNF-Î± OLE is closely related to analgesic and sedation effect. Further evaluations showed significant analgesic and sedative effects of OLE in tail-flick test and sedation test conducted in SD rats in vivo. All these results indicate that OLE has anti-inflammatory, analgesic and sedative effects both in vitro and in vivo.